2017
DOI: 10.5472/marumj.299393
|View full text |Cite
|
Sign up to set email alerts
|

A case of combined congenital anterior and posterior arch anomaly of C1 vertebra

Abstract: A case of combined congenital anterior and posterior arch anomaly of C1 vertebra C1 vertebranın kombine konjenital anterior ve posterior arkus anomalisi olgusu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…These statistics are in alignment with the results of the current study. Furthermore, Currarino’s Type A variations are identified as the most commonly reported anatomical anomaly of the atlas, with existing literature indicating a prevalence of 1.5–5% ( Guenkel et al, 2013 ; Geist et al, 2014 ; Souza et al, 2014 ; Ulusoy et al, 2017 ; Hyun et al, 2018 ; Cossu et al, 2019 ; Tsoucalas et al, 2020 ). This prevalence rate is corroborated by the 2.5% observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These statistics are in alignment with the results of the current study. Furthermore, Currarino’s Type A variations are identified as the most commonly reported anatomical anomaly of the atlas, with existing literature indicating a prevalence of 1.5–5% ( Guenkel et al, 2013 ; Geist et al, 2014 ; Souza et al, 2014 ; Ulusoy et al, 2017 ; Hyun et al, 2018 ; Cossu et al, 2019 ; Tsoucalas et al, 2020 ). This prevalence rate is corroborated by the 2.5% observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Currarino’s classification categorizes these variations into distinct types: Type A signifies a failure in the posterior midline fusion of the hemiarches; Type B represents a unilateral posterior cleft; Type C indicates a bilateral posterior cleft; Type D denotes a partial absence of the posterior arch with a residual posterior tubercle; and Type E encapsulates a complete absence of the posterior arch ( Currarino et al, 1994 ). Notably, congenital defects of the anterior arch were not initially included in Currarino’s framework; however, subsequent studies have identified instances of a cleft in the anterior arch accompanied by a partial or total absence of the posterior arch, termed “bipartite atlas” ( Weng et al, 2010 ; Guenkel et al, 2013 ; Ulusoy et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Split atlas (or bipartite atlas) is a rare congenital malformation consisting of the association of partial aplasia (or hypoplasia or defect or dehiscence) of the posterior and the anterior arches of C1 vertebrae [2]. It was considered by several authors as a “benign anatomical variation,” without clinical impact, and indeed almost all of the cases reported in the literature were discovered incidentally [3-6]. This malformation has been reported in only 0.1% of the population [7, 8].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In the case of an asymptomatic incidental finding, management is limited to clinical and radiological follow-up only. Conservative treatment with nonsteroidal anti-inflammatory drugs and usage of cervical orthosis or a halo ring may be proposed in case of chronic symptomatology without neurological deficit [3, 7, 23, 24]. In case of instability or neurological decompensation, OCJ fusion should be indicated using either the posterior or anterior approach.…”
Section: Discussion/conclusionmentioning
confidence: 99%